J-energy preserving well-posed linear systems - Staffans, Olof J. (Zielona Góra: Uniwersytet Zielonogórski)
The following is a short survey of the notion of a well-posed linear system. We start by describing the most basic concepts, proceed to discuss dissipative and conservative systems, and finally introduce J-energy-preserving systems, i.e., systems that preserve energy with respect to some generalized inner products (possibly semi-definite or indefinite) in the input, state and output spaces.
Keywords: well-posed linear system; system node; transfer function; Lax-Phillips semigroup; dissipative systems; conservative system; model theory; conservative realization; J-energy-preserving system; Lyapunov equations; Riccati equation